Unraveling current issues in scholarly publishing - Hare, Madelaine; Butler, Leigh-Ann (Canadian journal of information and library science, 2025)
This editorial introduces a special issue in the Canadian Journal of Information and Library Sciences on current issues in scholarly publishing. Ce texte éditorial présente un numéro spécial de la Revue canadienne des sciences de l’information et de bibliothéconomie consacré aux enjeux actuels de l’édition savante.